PENERAPAN VALUE ENGINEERING PEKERJAAN BANGUNAN BAWAH JEMBATAN PADA PEKERJAAN JEMBATAN LAMNYONG BANDA ACEH - Aulia Rahman (Universitas Teuku Umar, 2016)
This study aims to apply value engineering and analyze methods of construction on the bridge construction project conventional concrete construction. Evaluation is the execution of civil works on the building that is under construction bridge on the foundation structure. In the analysis of value engineering, there are several stages of implementing value engineering are the information phase followed by identifying the cost ranging from the highest costs to the lowest cost and use law Pareto chart table and then proceed to the creative stage by using the method of cost / worth and the last stage is the stage recommendation. From the results of application of value engineering preliminary design at a price of IDR. 72,486,508,196.71 then some alternatives that are alternatives I obtained the price of IDR. 40,616,598,222.56 or savings gained by 43.97% in this alternate entirely using precast concrete pile foundation alternative II IDR. 41,699,143,562.9 savings gained 42.47% in this alternative uses all pile foundations and alternate drill III IDR. 41,243,208,716.9. Savings gained by 43.10% in this alternative partly using precast concrete pile foundation and the pillar 5 and 6 using the bore pile coated steel casing. Elections under thebridge structure with value engineering is suggested should be done at the beginning of the project to optimize cost savings projects that better suit the purpose of value engineering itself.